The Merchant in Venice: Shylock’s „Unheimlich” Return - Henderson, Diana E. (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
The first decades of the new millennium have seen an odd return to origins in Shakespeare studies. The Merchant in Venice, a site-specific theatrical production realized during the 500th anniversary year of the “original” Jewish Ghetto, was not only a highlight among the many special events commemorating the 400th anniversary of Shakespeare’s death in 2016, but also a more creative and complex response to historicism. With her nontraditional casting of five Shylocks (developed through collaborations with scholars and students as well as her international, multilingual company), director Karin Coonrod made visible the acts of cultural projection and fracturing that Shakespeare’s play both epitomizes and has subsequently prompted. This article, written by a participant-observer commissioned to capture on video the making and performance of Compagnia de’ Colombari’s six-night run in the Campo del Ghetto Nuovo, explores the way this place is—and indeed, the category of place itself is always - a dynamic temporal construct, defying more complacent attempts at simple return (to home, to the text, to the past). Such a recognition allows nuanced, hybrid forms of multicultural theater and Shakespeare scholarship to emerge, and to collaborate more fruitfully.